2022
DOI: 10.2147/ijn.s337942
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Strain Mitigates Nanoparticle Internalization by Vascular Smooth Muscle Cells

Abstract: Background Intravascular delivery of nanoparticles for theranostic application permits direct interaction of nanoparticles and vascular cells. Since vascular smooth muscle cells (VSMCs), the major components of the vascular wall, are constantly subjected to mechanical stimulation from hemodynamic influence, we asked whether cyclic strain may modulate internalization of magnetic nanoparticles (MNPs) by cultured VSMCs. Methods Cyclic strain (1 Hz and 10%) was applied with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Researchers have also found that physiological cyclic stretch promotes the internalization of silica nanoparticles, which is related to cell stress and exocytotic events ( 142 ). Moreover, the changes in plasma membrane morphology by cyclic stretch will affect the distribution of actin and reduce the internalization of nanoparticles in VSMCs ( 143 ). Thus, understanding the role of nanoscale materials in endocytosis is important for investigating intracellular delivery and providing more targeted points for nanomedicine.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have also found that physiological cyclic stretch promotes the internalization of silica nanoparticles, which is related to cell stress and exocytotic events ( 142 ). Moreover, the changes in plasma membrane morphology by cyclic stretch will affect the distribution of actin and reduce the internalization of nanoparticles in VSMCs ( 143 ). Thus, understanding the role of nanoscale materials in endocytosis is important for investigating intracellular delivery and providing more targeted points for nanomedicine.…”
Section: Discussionmentioning
confidence: 99%
“… Cyclic stretch with frequency of 1 Hz and cyclic strain (5%, 10%, and 15%) [ 214 ] Tensile forces Flexcell® tension system (Flexcell Int.) Cyclic stretch with frequency of 1 Hz and 10% equibiaxial strain [ 192 ] Tensile forces Flexcell® tension system (Flexcell Int.) Cyclic stretch with frequency of 1 Hz and 5% cyclic elongation [ 208 ] Interstitial fluid pressure Xenograft tumors in nude mice implanted via subcutaneous injection of 1 × 10 6 cells in 50% Matrigel ~ 10–20 mmHg [ 194 ] TCPS, standard tissue culture polystyrene; PDMS, polydimethylsiloxane …”
Section: Models Of Physical Stimuli Used In Nanobio Researchmentioning
confidence: 99%
“…The analysis of effects of tensile forces on nanoparticle-cell interactions reveals that tensile forces (similarly with ECM stiffness of shear stress) may either promote or inhibit the uptake of nanoparticles by cells (Table 2 ). For example, the application of cyclic strain resulted in a significant reduction of nanoparticle uptake in vascular smooth muscle cells (VSMCs) [ 192 ]. This reduction was associated with the attenuation of microvilli and a decrease in vesicle size per cell, although not in the number of vesicles per cell [ 192 ].…”
Section: Effects Of Mechanical Stimuli On Nanoparticle Uptake By Cellsmentioning
confidence: 99%
See 2 more Smart Citations